Study of Reproductive & Thyroid Hormones in adolescent with Sickle Cell Disease - Sharja Phuljhele; Virendra K Kurrey; Akanksha Verma; Kanwaljeet Singh Hura (International Journal of Medical Research and Review, 2015)
Introduction: Sickle cell anaemia patients have been reported to suffer from endocrine dysfunctions which often have an influence on growth, development, and metabolism. Delayed somatic and sexual developments have been well described in patients with homozygous sickle cell disease. The present study focuses plasma levels of seven different endocrine hormones in individuals aged between 10-18 years, with a diagnosis of homozygous sickle cell disease.Material & methods: All study subjects were undergone for estimation of follicular stimulating hormone (FSH), Leuteinizing Hormone (LH), Testosterone, T3, T4 & TSH measured and value were analyse statistically.Observation: Study Patients with sickle cell disease showed LH, FSH Testosterone and Estradiol are significantly reduced in individual with homozygous sickle cell disease (SS) in comparison with control group suggest that the sickle cell gene abnormality has an adverse effect on endocrine functions.Conclusion: Routine screening for endocrine dysfunctions are advocated in all adolescent sickle cell disease patient.